Market Research of the Russian National and Regional Aspects of Builders Liability Insurance - Aleksander Andreevich Tsyganov; Denis Viktorovich Bryzgalov (Экономика региона, 2016)
The article studies the ways and level of the protection of the rights of shared construction participants in Russia, and the utilization of builders liability insurance for the purpose to identify the problem regions and the prospects of the development of mechanisms ensuring the liability of developers. The basis for the article was the study of real estate developers in 15 cities with the population over 1 million people. The article presents the data of the types of fund raising for building housing in the cities with the population over 1 million people, the regional differentiation in this parameter is highlighted. The article has explored the implementation of mechanisms ensuring the liability of developers for transfering premises to the shareholders. The main factors considered in the article are the form of registration of the relationship between a developer and an individual — an investor, as well as the mechanisms ensuring the liability of developers. It is shown that in some regions, the level of protection of the participants of shared construction is low. The mechanisms ensuring the liability of developers including the legal requirements for liability insurance and guarantee of credit institution are systematized. In the article, the key term of the liability insurance of builders for default on obligations or improperly performing the obligations on the delivery of residential properties, and also the condition of the guarantee of credit institution on the delivery of residential properties are considered. The regional features of how people participate in the construction of housing are described in the context of mechanisms ensuring the liability of developers. The use of various ensuring mechanisms, the differences in insurance by the commercial organizations and by joining the mutual society are shown. The results of the study can be used at the correction of the state and regional policy in the field of housing construction. In the article, it is shown that in the future, the strengthening of the value of financial mechanisms providing the liability insurance of developers should be expected in the connection of the growth of a number of incomplete housing for which the law provides a compulsory liability insurance of developers or security of credit organization